Multi-centre normative brain mapping of intracranial EEG lifespan patterns in the human brain - Woodhouse, Heather; Hall, Gerard; Simpson, Callum; Kozma, Csaba; Turner, Frances; Schroeder, Gabrielle M.; Diehl, Beate; Duncan, John S.; Mo, Jiajie; Zhang, Kai; Chari, Aswin; Tisdall, Martin; et al. (Brain Structure and Function, 2025)
Understanding healthy human brain function is crucial to identify and map pathological tissue within it. Whilst previous studies have mapped intracranial EEG (icEEG) from non-epileptogenic brain regions, they often neglect age and sex effects. Further, they are limited by small sample sizes due to the modality’s invasive nature. This study substantially expands the subject pool compared to existing literature, to create a multi-centre, normative map of brain activity which considers the effects of age, sex and recording hospital. Using interictal icEEG recordings from subjects across 15 centres, we constructed a normative map of non-pathological brain activity by regressing age and sex on relative band power in five frequency bands. A linear mixed model was implemented to account for the hospital effect. Variable importance was assessed using standard statistical measures, and regression coefficients (and their standard errors) were analysed at both whole-brain and regional scales. Recording hospital significantly impacted normative icEEG maps in all frequency bands, and age was a more influential predictor of band power than sex. The age effect varied by frequency band, but no spatial patterns were observed at the region-specific level. Certainty about regression coefficients was also frequency band specific and moderately impacted by sample size. The concept of a normative map is well-established in neuroscience research and particularly relevant to the icEEG modality, which does not allow healthy control baselines. Our key results regarding the hospital site and age effect guide future work utilising normative maps in icEEG.